(untitled) (World Bulletin of Education and Learning, 2025)
This study explores the theoretical foundations of the maqam and mode systems that have shaped Eastern musical traditions for centuries. By comparing historical and modern perspectives, it aims to analyze the modal structures, tonal hierarchies, and the spiritual-philosophical essence of maqam as a reflection of cultural identity. Drawing upon the works of both classical theorists and contemporary researchers, the research demonstrates that maqam represents not only a musical structure but also a complete aesthetic worldview integrating melody, emotion, and ethics. The paper also highlights the pedagogical importance of maqam theory in modern conservatory education and its relevance in preserving intangible cultural heritage in Central Asia and the Middle East.